African American perspectives on political science - Rich, Wilbur C. (Philadelphia : Temple University Press, 2007)
African American political scientists speak out about their discipline, academic issues and racism in the profession.
Introduction / Wilbur C. Rich -- Part one. Race and political scientists -- Still in the margins : the persistence of neglect of African American issues in political science, 1986-2003 / Ernest J. Wilson, III and Lorrie A. Frasure -- The race variable and the American Political Science Association's state of the discipline reports and books, 1907-2002 / Hanes Walton, Jr. and Robert C. Smith -- African American political scientists in academic wonderland / Wilbur C. Rich -- Part two. Globalization and transnational politics -- Black politics in Latin America : an analysis of national and transnational politics / Ollie A. Johnson, III -- Globalization and the study of development / Vernon D. Johnson -- Part three. Civic engagement and voting -- Political science and the study of African American public opinion / Melissa V. Harris-Lacewell -- A Black gender gap? Continuity and change in attitudes toward Black feminism / Evelyn M. Simien -- Going it alone : Black women activists and Black organizational quiescence / Andrea Y. Simpson -- Political scientists and the activist-technocrat dichotomy : the case of John Aubrey Davis / Martin Kilson -- Part four. Political institutions -- Dimensions of representation and the Congressional Black Caucus / Kenny J. Whitby -- Toward a critical race theory in political science : a new synthesis for understanding race, law, and politics / Barbara Luck Graham -- Presidential leadership and the politics of race : stereotypes, symbols, and scholarship / Wilbur C. Rich -- Part five. The subfields -- Comparative politics and Asia : contesting hegemonic inter- and intra-disciplinary boundaries / Germaine A. Hoston -- Race and the problem of equity in the administrative state : implications for political science theory and methods / Lenneal J. Henderson, Jr. -- Race and the city : the view from two political science journals / Marion Orr and Valerie C. Johnson -- Navigating the muddy waters of the mainstream : tracing the mystification of racism in international relations / Errol A. Henderson -- A critical review of American political institutions : reading race into the constitutional "silence" on race / Katherine Tate, Kevin L. Lyles, Lucius J. Barker -- Political science confronts Afro-America : a reconsideration / Jerry G. Watts.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Political science; Racism -- Political aspects; Racism -- Political aspects -- United States; African American political scientists -- Attitudes; Science politique; Racisme -- Aspect politique; Racisme -- Aspect politique -- États-Unis.; Politologues noirs américains -- Attitudes; political science; PHILOSOPHY -- Political; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; Political science; Racism -- Political aspects; United States; Politische Wissenschaft; USA; Schwärze; Politieke wetenschappen; Rassenvraagstuk; Verenigde Staten